Facile preparation of alkalized MXene with a larger interlayer for efficient removal of methylene blue - Ying Shi; Xiuying Fang; Yao Zhang; Mingrong Lu; Junxiu Ye; Min Yang; Hongbin Wang; Jiaxiong Li; Guizhen Li (Desalination and Water Treatment)
Ti3C2-MXene is one of the most studied MXenes which are new members of the two-dimensional (2D) material family. It can be fabricated and processed in a variety of scalable and cost-effective way. A novel adsorbent Ti3C2-NaOH was prepared by using NaOH as an intercalating agent to remove dyes in wastewater. The as-prepared Ti3C2-NaOH were analyzed by SEM, XRD, FTIR, Zeta, and BET techniques. The results demonstrate that the material exhibits significant interlayer spacing, with an expansion rate of ,39.94 %, a diverse array of functional groups (-OH, -F), and a considerable specific surface area, featuring pore sizes as large as 13.1969 nm. Furthermore, the effects of adsorbent dosage, initial concentration of MB, time, pH, and temperature on the removal of methylene blue (MB) by Ti3C2-NaOH were investigated. The adsorption capacity of Ti3C2-NaOH could reach 271 mg/g when the adsorption conditions were 20 mg of Ti3C2-NaOH, 293 K, 6 h, and pH 2–6. The adsorption process was well fitted by the Langmuir isotherm model and pseudo-second-order kinetic model. The thermodynamic experiment indicates that Ti3C2-NaOH adsorbing methylene blue is a spontaneous and exothermic process. The mechanisms for MB adsorption onto the Ti3C2-NaOH surface were mainly electrostatic attraction and hydrogen bonding. This work expands the application potential of Ti3C2-NaOH.